How does a network of Colombian interethnic women foster resilience to climate change and contribute to gender equality? - Howland, Fanny; Salas, Daniela (2024)
Integrating gender and intersectionality (G&I) into climate change (CC) policy cycles in Latin America remains insufficient, often relying on top-down approaches that overlook structural gender inequalities and local perspectives. Colombia provides a unique context, shaped by the 2016 Peace Accords and recent political shifts emphasizing marginalized groups, including women. However, fragmented implementation challenges policy coherence and effectiveness. This research examines the National Interethnic Women’s Network for Environmental Defense, which fosters climate-resilient agricultural practices, reduces gender inequalities, and influences policies. Using qualitative and quantitative methods, including Social Network Analysis, the study explores the network’s governance, advocacy, and impacts. It also assesses coherence between governmental and grassroots views on G&I in the context of CC.